POR UMA LITERATURA TEIMOSA - Alves Häckel, Thomas (LINKSCIENCEPLACE, 2026)
This study proposes a reflection on literature‟s role and place from Foucauldian thoughts, listing two main issues, through Deleuze‟s concepts: knowledge (statements, strata) and power (affection, non-stratified). From this starting point, the study is organized in four parts to question and reflect upon what literature is able to do. To that end, Rancière, Barthes and Diana Klinger‟s writings are used, in order to question whether there is a role or place for literary works or if they would not fit as power and stubbornness forces to make the world a more expressive place.